Discovering the mechanisms of abstraction in the performance of work teams in children to solve computational problems - Rodríguez, Patricia Paderewsky; Muñoz, René Fabián Zúñiga; Alegría, Julio Ariel Hurtado (My University, 2016)
The development of skills that allow children to perform satisfactorily in their training process and, later, in their work or social life, has become an objective for all educational and training models developed. This article deals with the relationship between thinking development skills, shared mental models and abstraction mechanisms, from a theoretical review and application with children aged between eight and twelve, from the Childprogramming methodology in a public education institution in Colombia. The results recorded at the end of the practices with this group of students, especially when assessing the progressive use of abstraction mechanisms in the Scratch environment, are presented, using the Dr. Scratch platform.